STRATEGI GURU DALAM PELAKSANAAN PROGRAM TAHFIDZ QUR’AN DI SDN CUGENANG KECAMATAN CUGENANG CIANJUR JAWA BARAT - Sajida, Diana; Yaskur, Muhammad; Al Mufti, Muflihin (UNISAN JURNAL, 2025)
This study aims to analyze the strategies used by teachers in implementing the Tahfidz Qur’an program at SDN Cugenang, Cugenang District, Cianjur, West Java. The Tahfidz Qur’an program is one of the efforts to enhance students’ ability to memorize the Qur’an from an early age. This research employs a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results indicate that teachers apply various strategies in the implementation of the Tahfidz Qur’an program, including the talaqqi method, muraja’ah, and motivation-based reward methods. Moreover, support from the school and parents plays a crucial role in the program’s success. Challenges encountered include differences in students’ memorization abilities, limited learning time, and insufficient supporting facilities. However, with the right strategies, the Tahfidz Qur’an program can be effectively implemented and positively impact students’ spiritual and academic development.